Development and Evaluation of Novel Methods to Improve Phage-Based Detection Methods - Kubala, Anton (2024)
Mycobacterial pathogens, such as M. tuberculosis, M. bovis and Mycobacterium avium ssp. paratuberculosis (MAP), pose significant and emerging global health risks for humans while mycobacterial disease in domesticated animals result in billions of dollars in losses to the agrarian industries, especially the dairy industry. Mycobacterial diseases are seen as endemic and persistent, with a lack of diagnostic tools able to detect mycobacterial infections quickly and with high sensitivity being the main hurdle to combating endemic mycobacterial infections. Due to the typically slow growth of mycobacteria such as MAP and M. bovis, current culture-based methods are too slow and classic microscopy is neither sensitive enough to detect low numbers of cells in clinical samples nor does it allow specific identification of the mycobacterial species encountered. PCR-based detection assays for both MAP and M. bovis exist and are able to produce a conclusive result in a few hours but they have limited sensitivity and cannot differentiate between live and dead organisms. The most common tool for the diagnosis of mycobacterial pathogens in animals are ELISA assays which are rapid, low cost and are reasonably specific but have low sensitivity, especially in the early stages of infection. To address all these issues, the Actiphage® assay was developed which utilises bacteriophage D29 to specifically infect and lyse mycobacterial cells recovered from a clinical blood sample and then PCR is used to identify species-specific signature sequences in the released mycobacterial DNA. This approach allows highly specific and sensitivity identification of the mycobacterial cells present in a blood sample within 24 h.